The ceramide activated protein phosphatase Sit4 impairs sphingolipid dynamics, mitochondrial function and lifespan in a yeast model of Niemann-Pick type C1 - Vilaça, R (2018)
The Niemann-Pick type C is a rare neurodegenerative disease that results from loss-of-function point mutations in NPC1 or NPC2, which affect the homeostasis of sphingolipids and sterols in human cells. We have previously shown that yeast lacking Ncr1, the orthologue of human NPC1 protein, display a premature ageing phenotype and higher sensitivity to oxidative stress associated with mitochondrial dysfunctions and accumulation of long chain bases. In this study, a lipidomic analysis revealed specific changes in the levels of ceramide species in ncr1Δ cells, including decreases in dihydroceramides and increases in phytoceramides. Moreover, the activation of Sit4, a ceramide-activated protein phosphatase, increased in ncr1Δ cells. Deletion of SIT4 or CDC55, its regulatory subunit, increased the chronological lifespan and hydrogen peroxide resistance of ncr1Δ cells and suppressed its mitochondrial defects. Notably, Sch9 and Pkh1-mediated phosphorylation of Sch9 decreased significantly in ncr1Δsit4Δ cells. These results suggest that phytoceramide accumulation and Sit4-dependent signaling mediate the mitochondrial dysfunction and shortened lifespan in the yeast model of Niemann-Pick type C1, in part through modulation of the Pkh1-Sch9 pathway.